Protein Produced by Bacillus subtilis ATCC21332 in the Presence of Cymbopogon flexuosus Essential Oil - Noor H.M.; Muhamad H.S.; Ismail I.N.A.; Radzi S.M.; Rehan M.M.; Kader A.J.A.; Mohamad R. (Trans Tech Publications Ltd, 2024)
Indexed by WOS/SCOPUS